Sediment Dynamics in Artificial Nourishments - Coelho, Carlos Daniel Borges (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Serious erosion problems related to significant negative sediment budgets in coastal systems have been identified worldwide. Artificial nourishments are a coastal erosion mitigation strategy that allows these negative budgets to be decreased by adding sediment to a coastal system. However, due to the complexity of coastal processes, it is difficult to evaluate sediment dynamics after the intervention. In consideration of this, this Special Issue disseminates the most updated scientific knowledge on understanding the sediment dynamics processes after artificial nourishments.